Tinjauan Hukum Islam Terhadap Investasi - Sahil, Irdlon (INAIFAS Press, 2021)
This study is intended to explain the Islamic law review of investment. This research method is carried out by reading reference books, journals and other media related to investment. This research shows that investment is an activity to place funds in one or more types of assets during a certain period with the hope of earning income and / or an increase in investment value in the future. In investing, Islam has described good and correct procedures to avoid losses. The legal basis regarding investment is contained in several verses in the Al-Qur'an, including: QS. al-Baqarah: 261, QS. An-Nisa ':: 9, Lukman: 34 and al-Hasyr: 18. Islam allows investment on condition that the investment must meet the rules in accordance with Islamic law.